Counseling Strategies for Prospective Brides and Grooms in Realizing a Harmonious, Loving, and Compassionate Family (Sakinah, Mawaddah, Rahmah) from the Perspective of Islamic Law (A Case Study at the Office of Religious Affairs/KUA, West Palu District) - Andri, Andri; Nasaruddin, Nasaruddin; Hilal Malarangan; Moh. Jamil (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2025)
This study examines the counseling guidance strategies implemented by the Office of Religious Affairs in West Palu District to prepare bride and groom candidates for establishing a Sakinah Mawaddah Warahmah household. Using a qualitative approach with a case study design, the research analyzes these strategies through the lens of Islamic Law. Data were collected through interviews, observations, and documentation. The findings reveal that the counseling process integrates religious values and psychological approaches to provide candidates with essential knowledge regarding marital rights, duties, and conflict resolution. From the perspective of Islamic Law, these strategies serve as a preventive measure (Sadd al Dhari’ah) to minimize divorce rates and ensure family stability. This study concludes that structured premarital counseling is vital for achieving the maqasid al shari’ah of preserving lineage and creating a harmonious family foundation..